ANALISIS QUALITY FUNCTION DEPLOYMENT (QFD) PADA RANCANG BANGUN MESIN MILLING 3 SUMBU - Rizal, Syamsul; Rifki, Muhammad; Malik, Irawan; Zamheri, Ahmad (MACHINERY Jurnal Teknologi Terapan, 2023)
Machines are a special concern in the production process of several parties who use CNC machines, including industrial companies, educational institutions such as universities, polytechnics and vocational high schools. Machines used in industry and agencies with various brands, the price reaches hundreds of millions per unit and even billions of rupiah, other commercial CNC Mini Milling is still relatively expensive, and also has a heavy weight. The purpose of this study was to determine the customer's desire on the CNC Mini Milling machine, by conducting a questionnaire to increase customer satisfaction. Therefore, in this study, an analysis of customer satisfaction was carried out using the Quality Function Deployment (QFD) method in order to design a design according to the customer's wishes. The results of the study can be used as material to make improvements to material specifications, material capabilities and appropriate dimensions. The results of this study have found things that must be prioritized based on the House of Quality. Some of the priorities include having to repair the frame at a low price, light and strong, can increase ST 37, easy to use and dimensions that are not too big.